Successful live birth following preimplantation genetic diagnosis for phenylketonuria in day 3 embryos by specific mutation analysis and elective single embryo transfer - Lavery, S; Abdo, D; Kotrotsou, M; Trew, G; Konstantinidis, M; Wells, D (Springer Berlin Heidelberg, 2012)
Phenylketonuria (PKU) is an autosomal recessive inherited metabolic disorder caused by a complete or near-complete deficiency of the liver enzyme phenylalanine hydroxylase (PAH), which converts the amino acid phenylalanine to tyrosine, leading to the increase of blood and tissue concentration of phenylalanine to toxic levels. PKU is not life threatening but is treated through lifelong dietary management. If untreated, it can lead to severe learning disability, brain function abnormalities, behavioural and neurological problems. The non-life threatening nature of PKU has until now caused some debate on whether to licence its detection by preimplantation genetic diagnosis (PGD). We report the first successful live birth in the UK following single cell embryo biopsy and PGD for the detection of two different mutations in the (PAH) gene. This case highlights both an important scientific development as well as the ethical challenge in offering couples who carry PKU this new reproductive option when starting their family.